Clinical informationist participation in grand round sessions of gastroenterology department: An action research study - Elahe Zare-Farashbandi; Peyman Adibi; Alireza Rahimi; Firoozeh Zare-Farashbandi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Nowadays, providing access to the required information by clinical informationist (CI) is vital for clinical teams to make the best decision. This study was carried out to identifying how CIs should participate in grand round (GR). MATERIALS AND METHODS: The current study is an action research study. It was conducted in the GR sessions of the Gastroenterology department of Al-Zahra Hospital affiliated with Isfahan University of Medical Sciences in 2017. Participants included attending physicians, fellowship students of the Gastroenterology departments, a CI, and two supervising medical librarians. Data were collected through observation and discussion. Qualitative content analysis and concept mapping were used for data analysis. RESULTS: The findings indicated that existing problems were related to the CI, medical team, and infrastructural ones. The participation of the CI in medical team was arranged based on the following steps: planning, action, evaluation, and suggestions. It started from an initial diagnosis of patients and ended in GR meetings. During evaluation step, suggestions were made to remove the existing problems and in the fifth step, results were summarized and a framework for the participation of the CI in GR sessions was suggested. CONCLUSIONS: Medical team members were satisfied with the participation of the CI, but it is necessary to remove the existing structural and personal barriers (related to the CI and medical team members), in order to improve the efficiency of this participation.